2019
DOI: 10.3892/ijo.2019.4765
|View full text |Cite|
|
Sign up to set email alerts
|

miR‑802 inhibits the aggressive behaviors of non‑small cell lung cancer cells by directly targeting FGFR1

Abstract: Emerging reports have revealed that several microRNAs (miRNAs) are abnormally expressed in non-small cell lung cancer (NSCLC). miRNAs have been identified as oncogenes or tumor suppressors, and regulate various biological processes including oncogenesis and development. miR-802 is dysregulated in multiple types of human cancer, and exerts tumor-suppressive or promoting roles. However, the expression levels and functional roles of miR-802 in NSCLC remain largely unknown. In the present study, miR-802 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 45 publications
4
24
0
Order By: Relevance
“…Zhang et al 34 reported that miR‐802 promoted cell proliferation and inhibited cell apoptosis in human cervical cancer 33 . MiR‐802 also suppressed non–small cell lung cancer development by regulating FGFR1 34 . Consistently, our findings suggested that overexpression of miR‐802 suppressed cell growth, migration, and invasion in GC cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Zhang et al 34 reported that miR‐802 promoted cell proliferation and inhibited cell apoptosis in human cervical cancer 33 . MiR‐802 also suppressed non–small cell lung cancer development by regulating FGFR1 34 . Consistently, our findings suggested that overexpression of miR‐802 suppressed cell growth, migration, and invasion in GC cells.…”
Section: Discussionsupporting
confidence: 86%
“…Zhang et al 34 reported that miR-802 promoted cell proliferation and inhibited cell apoptosis in human cervical cancer. 33 MiR-802 also suppressed non-small cell lung cancer development by regulating FGFR1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-377 expression is remarkably downregulated in NSCLC tissues, and thus contributing to inhibited cell proliferation and development as a tumor-suppressor gene. 11,18 Similarly, our experimental data suggested that miR-377-5p was significantly reduced in vivo and in cell models, and lessened cell viability, proliferation, migration, and invasion. Furthermore, we observed that miR-377-5p overexpression-induced cell-cycle arrest, the numbers of G0/G1-phase cells were increased and that of S-phase cells were reduced, which were consistent with previous studies.…”
Section: Discussionsupporting
confidence: 59%
“…To date, several miRNAs have been reported to inhibit cell metastasis by targeting AKT1 in cancers. 17,18 However, the effects and regulation mechanisms between miR-377 and AKT1 has not been elucidated. To investigate the effects of miR-377-5p and/or AKT1 on the development, invasion, and metastasis of lung carcinoma, we measured their expressions in cancer tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that overexpression of Cdk6 promoted the progression of lung adenocarcinoma, 48 and downregulation of Cdk6 inhibited the progression of NSCLC. 49 The present study demonstrated that HNF1A-AS1 promoted the progression of NSCLC via upregulation of Cdk6. In addition, due to the complicated molecular mechanism of NSCLC progression, the effects of HNF1A-AS1 on epithelial-mesenchymal transition, autophagy or apoptosis of NSCLC need to be further explored.…”
Section: Discussionsupporting
confidence: 53%